Regulation of death receptor-mediated apoptosis pathways - Schmitz, Ingo; Kirchhoff, Sabine; Krammer, Peter H. (International journal of biochemistry & cell biology, 2000)
Apoptosis or programmed cell death can be induced by a variety of stimuli including activation of death receptors. This subgroup of the TNF/NGF-receptor-superfamily activates caspases, a family of aspartyl-specific cysteine-proteases, which are the main executioners of apoptosis. Depending on the cell type, signalling pathways downstream of the death receptors can be modulated by different proteins such as Bcl-2, FLIPs, chaperones and kinases. Deregulation of apoptosis has been associated with diseases as cancer, autoimmunity and AIDS. Therefore, the identification of modulators of apoptosis has several therapeutic implications.
Gesehen am 03.03.2021